The possible impact of animals on Job"s body image: A psychoanalytical perspective - Zwan, Pieter van der (HTS teologiese studies, 2021)
The body plays an important role in the book of Job – as do animals. According to psychoanalytical specifically object-relations theory, a subjective body image was partly constructed through the internalisation of external stimuli from significant others who mirrored the subject through their feedback or through their own bodies, which served as an ideal or critique to the subject. Amongst the external stimuli, animals constitute such significant others. Animals could therefore have impacted Job’s subjective body image, particularly as their bodies were described in detail by God as a response to Job’s complaints and searching.Contribution: Two theoretical and interrelated problems were acknowledged although they cannot be satisfactorily solved: the cultural aspect of the body image and the relationship to animals.